Cambridge Phrasal Verbs Dictionary - Walter E. Elizabeth (Cambridge, Cambridge University Press, 2006)
The new edition of the Cambridge Phrasal Verbs Dictionary covers around 6,000 phrasal verbs current in British, American, and Australian English. Clear explanations and guidance help learners master this difficult yet essential aspect of the English language. Fully updated with new phrasal verbs, e.g. cosy up to, copy in, sex up Clear advice on grammar and usage Thousands of example sentences show phrasal verbs in typical contexts Most common phrasal verbs highlighted so students know which to learn A thematic section shows phrasal verbs in topic groups for vocabulary expansion This new edition of the Cambridge Phrasal Verbs Dictionary provides clear and simple explanations of around 6,000 phrasal verbs current in British, American and Australian English today.